2018
DOI: 10.1002/marc.201800533
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Synthesis of Peptoid Arrays via Laser‐Based Stacking of Multiple Polymer Nanolayers

Abstract: Here, the combinatorial synthesis of molecule arrays via a laser‐assisted process is reported. Laser‐transferred polymer nanolayers with embedded monomers, activators, or bases can be reliably stacked on top of each other, spot‐by‐spot, to synthesize molecule arrays. These various chemicals in the nanometer‐thin layers are mixed by heat or solvent vapor, inducing coupling reactions. As an example, peptoid arrays with a density of 10 000 spots per cm2 with the sub‐monomer or monomer method are generated. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Advances in technology development, which for example rely on the patterning of co‐polymers for the synthesis of biomolecules, [ 24 ] make the rapid production of peptide microarrays feasible. [ 25–27 ] High‐density peptide microarrays have been used for the development of diagnostic biomarkers, for example, in Malaria, Zika virus, and Chagas disease, [ 28–30 ] as well as in the analysis of therapeutic antibodies against C. difficile . [ 31 ] Additionally, epitopes recognized by antibodies elicited after vaccination against infectious diseases, such as Tuberculosis, Malaria, and Tetanus, can be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in technology development, which for example rely on the patterning of co‐polymers for the synthesis of biomolecules, [ 24 ] make the rapid production of peptide microarrays feasible. [ 25–27 ] High‐density peptide microarrays have been used for the development of diagnostic biomarkers, for example, in Malaria, Zika virus, and Chagas disease, [ 28–30 ] as well as in the analysis of therapeutic antibodies against C. difficile . [ 31 ] Additionally, epitopes recognized by antibodies elicited after vaccination against infectious diseases, such as Tuberculosis, Malaria, and Tetanus, can be identified.…”
Section: Introductionmentioning
confidence: 99%
“…This approach may serve as a basis to generate large and complex compound collections for the multivalent display of many different glycans in an orthogonal synthesis strategy. With our laser-based approach, molecules can be synthesized directly on surfaces step-by-step, by "printing" and stacking solid polymer nanolayers, 51,191 which embed all kinds of different chemicals and building blocks. Especially for peptide synthesis and applications in disease research, this offers a rapid strategy to generate diverse microarrays.…”
Section: Discussionmentioning
confidence: 99%
“…The combinatorial laser-induced transfer method (cLIFT) helps to circumvent contamination and clogging issues. 50 Currently the method is restricted to the chemical synthesis of peptide and peptoid 51 arrays, but may be expanded to glycan array synthesis. Novel micro-and nanoprinting technologies exploit cantilevers from atomic force microscopy to pattern surfaces, such as the wellknown dip-pen nanolithography.…”
Section: Printing On Surfacesmentioning
confidence: 99%
“…Indeed, Löffler and co‐workers61a clearly showed that a nanoscale activation layer ( N , N ′‐diisopropylcarbodiimide (DIC) and hydroxybenzotriazole (HOBt)) stacked over nanoscale matrix‐embedded nonactivated Fmoc‐protected amino acid building blocks could couple these in situ activated amino acids to the solid support. In 2018, Mattes et al used the 2D laser‐scanner system to stack up to four different nanoscale material layers on top of each other to generate peptoid arrays via the monomer and submonomer method. Upon melting, Fmoc‐protected N‐substituted glycine derivatives, embedded in matrix material, diffused through three nanometer‐thin layers into an immobilized polymer film on a glass slide.…”
Section: Miniaturized Synthesis and Molecule Librariesmentioning
confidence: 99%